Improved luminosity determination in pp collisions at s√ = 7 TeV using the ATLAS detector at the LHC - Aad, G. (2013)
The luminosity calibration for the ATLAS detector at the LHC during pp collisions at sqrt(s) = 7 TeV in 2010 and 2011 is presented. Evaluation of the luminosity scale is performed using several luminosity-sensitive detectors, and comparisons are made of the long-term stability and accuracy of this calibration applied to the pp collisions at sqrt(s) = 7 TeV. A luminosity uncertainty of Delta L/L = +/- 3.5% is obtained for the 47 pb-1 of data delivered to ATLAS in 2010, and an uncertainty of Delta L/L = +/- 1.8% is obtained for the 5.5 fb-1 delivered in 2011.